Kajian Strategi Pengurangan Sampah dan Potensi Penerapan Ekonomi Sirkuler Pada Pengelolaan Sampah di Kabupaten Toba Sumatera Utara: Study of Waste Reduction Strategy and The Potential Application of Circular Economy in Solid Waste Management in Toba Regency of North Sumatera - GEBY OTIVRIYANTI; REGINA DEA TILOTTAMA; SOPHIA SHANTI MEILANI; AYUDIA MUTIARA FANI; WAHYU PURWANTA (BRIN Publishing (Penerbit BRIN), 2023)
ABSTRACT One of the factors for the competitiveness of tourist destinations is cleanliness, especially solid waste management. Toba Regency, as one of the buffer zones for the tourist destination of Lake Toba, cannot be separated from the challenge of reducing and handling solid waste generated by households, industry, and tourists. The amount of waste generated in Toba Regency in 2022 is 31,794 tons/year with a reduction rate of 0.94%, 37% dumped in landfill and 62% unmanaged. A simulation was carried out through data analysis from various planning documents, field observations, and interviews with stakeholders to get the best scenario for achieving the Jakstranas waste target in this study. Scenario 1 is by maximizing recycling through waste banks with a capacity of 10,074 tons/year or scenario 2 by composting food waste as much as 7,665 tons/year and recycling through waste banks at 2,317.75 tons/year. Scenario 1 is more likely to be implemented than scenario 2, considering the low compost market. If scenario 1 is implemented, the potential for creating a circular economy ranges from Rp. 19,654,374,000 to Rp. 22,354,206,000 annually. ABSTRAK Salah satu faktor daya saing destinasi wisata adalah kebersihan, khususnya pengelolaan sampah. Kabupaten Toba sebagai salah satu wilayah penyangga destinasi wisata Danau Toba tidak lepas dari tantangan untuk mengurangi dan menangani sampah yang dihasilkan baik oleh rumah tangga, industri, maupun wisatawan. Jumlah timbulan sampah Kabupaten Toba tahun 2022 sebanyak 31.794 ton/tahun dengan tingkat pengurangan sebesar 0,94%, ditimbun di Tempat Pemrosesan Akhir (TPA) 37% dan tidak terkelola 62%. Melalui analisis data dari berbagai dokumen perencanaan, pengamatan lapangan dan wawancara dengan pemangku kepentingan dilakukan simulasi untuk mendapatkan skenario terbaik dalam mencapai target Jakstranas persampahan dalam studi ini. Skenario 1 dengan memaksimalkan daur ulang melalui bank sampah dengan kapasitas 10.074 ton/tahun atau skenario 2 dengan melakukan pengomposan sampah sisa makanan sebanyak 7.665 ton/tahun dan daur ulang melalui bank sampah 2.317,75 ton/tahun. Skenario 1 lebih mungkin dilaksanakan dibanding skenario 2 mengingat rendahnya pasar kompos. Jika skenario 1 terlaksana maka potensi terwujudnya ekonomi sirkuler berkisar antara Rp. 19.654.374.000 hingga Rp. 22.354.206.000 per tahun